Dynamics and Bifurcation of Patterns in Dissipative Systems - Dangelmayr, G. (Gerhard), 1951-; Oprea, Iuliana (World Scientific series on nonlinear science. Special theme issues and proceedings, 2004)
Understanding the spontaneous formation and dynamics of spatiotemporal patterns in dissipative nonequilibrium systems is one of the major challenges in nonlinear science. This collection of expository papers and advanced research articles, written by leading experts, provides an overview of the state of the art. The topics include new approaches to the mathematical characterization of spatiotemporal complexity, with special emphasis on the role of symmetry, as well as analysis and experiments of patterns in a remarkable variety of applied fields such as magnetoconvection, liquid crystals, gran.